Determination of ergosterol as a potential biomarker in pathogenic medically important fungal isolates - Ahmad Sh. A. Lafi,; Jacinta Santhanam,; Tzar Mohd Nizam Khaithir,; Nur Fashya Musa,; Fahrul Huyop, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Ergosterol, a component of fungal cell membrane, has been frequently detected as an indicator of fungal presence and mass in environmental samples like soil. However, its detection in major pathogenic fungal species has not been investigated. In this study, the ergosterol contents of ten pathogenic fungal species were determined. Liquid chromatography was used for the detection and quantification of ergosterol extracted from fungal broth cultures. Results showed that ergosterol eluted as a single, well resolved peak in the chromatogram profiles of all tested fungi. Based upon relative amounts of ergosterol produced per fungal mycelial dry weight, three groups of fungal pathogens were identified, namely low ergosterol (Aspergillus niger, Candida albicans and Cryptococcus neoformans at 4.62, 6.29 and 7.08 μg/mg, respectively), medium ergosterol (Fusarium solani, Aspergillus fumigatus, Mucor sp., Penicillium sp., Cryptococcus gattii and Rhizopus sp. at 9.40, 10.79, 10.82, 11.38, 12.60 and 13.40 μg/mg, respectively), and high ergosterol (Candida tropicalis at 22.84 μg/mg), producers. Ergosterol was not detectable in bacterial samples, which were included as controls. This first report on ergosterol detection in major pathogenic fungal species indicates that ergosterol may be used as a biomarker to diagnose invasive fungal infections in clinical samples.